Pressure‐Stable Air‐Retaining Nanostructured Surfaces Inspired by Natural Air Plastrons. Issue 13 (4th May 2018) - Vüllers, Felix; Germain, Yann; Petit, Luce‐Marie; Hölscher, Hendrik; Kavalenka, Maryna N.
Abstract: Inspired by the pressure‐stable air layers retained by surfaces of aquatic insects, a technique is introduced to support the air–water interface on submerged superhydrophobic surfaces by pressurizing the retained air layer. This pressurization increases retained air layer stability against elevated and fluctuating hydrostatic pressures. Based on the movement of the air–water interface during wetting transition on superhydrophobic nano‐ and microhaired nanofur surface, the correlation between material surface energy, topography, and air layer stability is studied. By perforating nanofur, precise control over the air pressure in the underwater retained air layer is gained and the stability of the air–water interface against hydrostatic pressure is improved by several orders of magnitude compared to unsupported artificial superhydrophobic surfaces. 86% of the retained air layer on pressure‐supported perforated nanofur is intact up to 4 bar hydrostatic pressure, which corresponds to a water depth of 40 m. Furthermore, the influence of perforation parameters, such as number and distribution of pores on the stability of the retained air layer, is investigated. Finally, the stability of the air–water interface against fluctuations in water pressure up to an additional pressure of 3 bar is demonstrated by introducing a buffer air pressure in the retained air layer. Abstract : Inspired by the pressure‐stable plastron of natural superhydrophobic surfaces, a mechanism is developed to control and support the pressure in the retained air layer of perforated artificial superhydrophobic surfaces. The possibility to adjust the retained air pressure is exploited to enhance the air–water interface stability against elevated hydrostatic pressures, as well as pressure fluctuations and prolonged immersion.